B7 immune-checkpoints as targets for the treatment of neuroendocrine tumors. Issue 2 (February 2021) - Yuan, Ziqiang; Gardiner, Juliet C; Maggi, Elaine C; Huang, Shuyu; Adem, Asha; Bagdasarov, Svetlana; Li, Guiying; Lee, Sylvia; Slegowski, Daniel; Exarchakis, Alyssa; Howe, James R; Lattime, Edmund C; et al.
Abstract : The B7 family, and their receptors, the CD28 family, are major immune checkpoints that regulate T-cell activation and function. In the present study, we explore the role of two B7 immune-checkpoints: HERV-H LTR-Associating Protein 2 (HHLA2) and B7 Family Member, H4 (B7x), in the progression of gastrointestinal and pancreatic neuroendocrine tumors (GINETs and PNETs). We demonstrated that both HHLA2 and B7x were expressed to a high degree in human GINETs and PNETs. We determined that the expression of B7x and HHLA2 correlates with higher grade and higher incidence of nodal and distant spread. Furthermore, we confirmed that HIF-1α overexpression is associated with the upregulation of B7x both in our in vivo (animal model) and in vitro (cell culture) models. When grown in vitro, islet tumor β-cells lack B7x expression, unless cultured under hypoxic conditions, which results in both hypoxia-inducible factor 1 subunit alpha (HIF-1α) and B7x upregulation. In vivo, we demonstrated that Men1/B7x double knockout (KO) mice (with loss of B7x expression) exhibited decreased islet β-cell proliferation and tumor transformation accompanied by increased T-cell infiltration compared with Men1 single knockout mice. We have also shown that systemic administration of a B7x mAb to our Men1 KO mice with PNETs promotes an antitumor response mediated by increased T-cell infiltration. These findings suggest that B7x may be a critical mediator of tumor immunity in the tumor microenvironment of NETs. Therefore, targeting B7x offers an attractive strategy for the immunotherapy of patients suffering from NETs.